CONTROLLED CHAOS AS A TOOL FOR RADICAL SOCIAL CONSTRUCTION OF CONTEMPORARY IN THE CONTEXT OF GLOBAL CHALLENGES - Ordenov, Serhii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The problem of interaction of regions, cultural centers, countries, societies at different stages of their development is significantly updated in the globalized world. One of the manifestations of globalization is the uneven economic and sociocultural development of different peoples, regions, civilizations, etc. which makes this problem worse. In the course of interaction in the globalized world, societies use various technologies to influence each other’s behavior as much as possible. The aim is the implementation of a philosophical analysis of controlled chaos as a tool of radical social construction of the present in the context of global challenges. Research methodology. The research used dialectical and synergistic methods in their integrative combination. Research results. Since the moment of its appearance, "chaos theory" developed as a mathematical concept, but later it spread to other fields of knowledge, including humanitarian ones. To a large extent, this is facilitated by the development of the interdisciplinary science of synergetics. Some Western researchers studying complex dynamic non-linear social systems (especially political ones) depart from the understanding of social processes from the position of recognizing the mutual influence of a certain number of factors leading to the stabilization of relations, and focus on what contributes to the formation of chaos (S. Mann). Given that these systems always contain factors that push them beyond stability, the scientists believe that it is necessary to increase the exploitation of this criticality, using it as a tool to spread chaos to ensure US national interests. In this way, the developed economies of the world have the opportunity to influence the transitional countries, determining their place in the global economic system. Discussion. The usage of the social technology of "controlled chaos" in geopolitics leads to an artificial increase in entropy and the spread of destructiveness to the social spheres of developing societies. This technology use causes divergent changes in the structure of social relations, which make social development and structural restructuring impossible, thereby institutionalizing their transitivity as a liminal phase, which becomes a certain type of stationary state of transitional societies. Conclusions. Such activity leads to deepening of social and natural problems called "global challenges". This especially applies to the problems related to the preservation of peace and stability, because the use of radical social technologies of significant influence to other societies dramatically increases conflictuality in the world.